High Photoresponsivity Ru-doped ZnO/p-Si Heterojunction Diodes by the Sol-gel Method - Karatas, Sukru; El-Nasser, H. M.; Al-Ghamdi, Ahmed. A.; Yakuphanoğlu, Fahrettin (Springer, 2018)
The ruthenium (Ru) doped nanostructure ZnO films were prepared by the sol-gel spin coating method. Undoped and Ru doped ZnO films are formed as fibers. The optical band gaps of undoped, 0.1 at.% and 0.5 at.% Ru doped ZnO films were found to be 3.31, 3.30 and 3.29 eV, respectively. The electrical properties of undoped and Ru-doped ZnO/p-Si heterostructure diodes were investigated under dark and visible light illuminations using current-voltage (I-V) measurements. The diodes exhibit a non-ideal I-V behavior due to the interfacial layer and the series resistance. The electrical parameters such as ideality factors, barrier heights and series resistances obtained from different methods were determined under illumination conditions. The diode having 0.1 at.% Ru doped ZnO exhibited the highest photoresponse of 7.75 x 10(3) under 100 mW/cm(2). The obtained results indicate that the photoresponsivity properties of the ZnO based photodiode can be improved with Ru content.
Keywords: Zinc oxide; Thin solid films; Sol-gel growth; Electrical properties